Revitalisasi Dakwah Melalui Perencanaan Mutu: Tinjauan Kritis dan Adaptasi Framework Perencanaan Mutu untuk Organisasi Dakwah - Riza Lirizki (STID Al Hadid Surabaya, 2023)
Da'wah organizations need to implement quality planning for organizational development and realize their missionary mission. However, references related to the concept of quality planning that are usually used come from the context of profit organizations, especially manufacturing companies, which are in different conditions from the context of da'wah organizations. Therefore, it is necessary to propose adaptations in the use of a quality planning framework for da'wah organizations. This study aims to provide a critical review and proposal for adapting a quality planning framework for da'wah organizations. The research method used is a qualitative-theoretical approach in the basic research paradigm. The results of this study indicate that quality management is very important in the development of da'wah organizations. Quality planning in da'wah organizations is oriented towards achieving missionary missions and increasing productivity. In compiling a quality plan, it is necessary to determine in advance the organization's quality policy as a guideline for quality improvement. The process of evaluating and improving quality does not have to use the benchmarking and statistical approach that is usually used in the context of manufacturing companies. The output of quality planning in the context of da'wah organizations must contain the features of da'wah products that are in accordance with organizational values ​​and customer expectations and the best process design accompanied by an appropriate and effective process control system. Keywords: Critical Review, Proposal, Framework, Quality Planning, Da’wah Organization